Smooth muscle-specific deletion of nitric oxide-sensitive guanylyl cyclase is sufficient to induce hypertension in mice - Groneberg, Dieter; König, Peter; Wirth, Angela; Offermanns, Stefan; Koesling, Doris; Friebe, Andreas (Circulation, 2010)
Background— Arterial hypertension is one of the major diseases in industrial countries and a major cause of mortality. One of the main vascular factors responsible for the relaxation of blood vessels and regulation of blood pressure is nitric oxide (NO). NO acts predominantly via NO-sensitive guanylyl cyclase (NO-GC), which is made up of 2 different subunits (α and β). Deletion of the β1 subunit leads to a global NO-GC knockout, and these mice are hypertensive. However, global deletion of NO-GC in mice does not allow identification of the cell/tissue type responsible for the elevated blood pressure. - - Methods and Results— To determine the relative contribution of smooth muscle cells to the hypertension seen in NO-GC knockout mice, we generated smooth muscle-specific knockout mice for the β1 subunit of NO-GC using a tamoxifen-inducible system. Male mice were investigated because the Cre transgene used is located on the Y chromosome. Tamoxifen injection led to a rapid reduction of NO-GC expression in smooth muscle but did not affect that in other tissues. Parallel to a reduction in NO-induced cGMP accumulation, NO-induced relaxation of aortic smooth muscle was gradually lost after induction by tamoxifen. Concomitantly, these animals developed hypertension within 3 to 4 weeks. - - Conclusions— We generated a model in which the development of hypertension can be visualized over time by deletion of a single gene in smooth muscle cells. In sum, our data provide evidence that deletion of NO-GC solely in smooth muscle is sufficient to cause hypertension.